2000
DOI: 10.1038/sj.sc.3101087
|View full text |Cite
|
Sign up to set email alerts
|

Paraplegia caused by painless acute aortic dissection

Abstract: Objectives: Painless acute aortic dissection in which paraplegia is the only presenting sign is rare, with limited reported cases. Case report: The authors report a patient with painless acute aortic dissection who presented with sudden onset paraplegia. Ischemic diseases of the spinal cord were suspected as the cause. MRI revealed extensive acute aortic dissection with an intramural hematoma. The patient was treated conservatively by strictly controlling his blood pressure. The treatment was successful, altho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 21 publications
1
29
0
Order By: Relevance
“…The fact that patients do not define pain is a factor that makes aortic dissection diagnosis difficult and delays the treatment of the patient. The reported painless aortic dissection rate in the literature ranges between 5-15% (7,11,12,14). Recent studies revealed that indicators of the inflammatory reaction white blood cells, PLTc and D-dimer level, are closely associated with clinical outcomes in aortic events (24)(25)(26)(27)(28)(29)(30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that patients do not define pain is a factor that makes aortic dissection diagnosis difficult and delays the treatment of the patient. The reported painless aortic dissection rate in the literature ranges between 5-15% (7,11,12,14). Recent studies revealed that indicators of the inflammatory reaction white blood cells, PLTc and D-dimer level, are closely associated with clinical outcomes in aortic events (24)(25)(26)(27)(28)(29)(30).…”
Section: Discussionmentioning
confidence: 99%
“…These cases generally apply with cardiac or neurological complaints. Congestive heart failure vena cava superior syndrome, paraplegia, syncope, repeating transient ischemic attacks, temporary loss of motor and sense in the legs along with hoarseness are among painless AAD complaints (7,(10)(11)(12)(13)(14)(15). Atypical presentations may delay the diagnosis of this disease.…”
Section: Introductionmentioning
confidence: 99%
“…In 17-40% of patients with DAs, neurologic symptoms can be manifested 6,10,11,17) . The causes of ischemic neurologic deficits are occlusions of main feeding arteries, such as the carotid, vertebral, and spinal arteries, or vasa nervorum of the peripheral nerves, or hypotension-induced perfusion failures 12) , which can induce ischemic stroke, spinal cord ischemia, ischemic neuropathy, hypoxic encephalopathy, or syncope.…”
Section: Discussionmentioning
confidence: 99%
“…2 However, painless paraplegia, as in this case, is exceedingly rare and limited to six case reports. [3][4][5][6][7][8] Paralysis in AD is due to anterior spinal artery syndrome, which usually includes loss of pain and temperature sensation, with preservation of vibration and proprioception sensation. This pattern typically manifests after spinal shock resolves over weeks.…”
mentioning
confidence: 99%